Effect of Defoliation Age on The Production and Energy Value of Indian Bluegrass (Bothriochloa pertusa) - I Gusti Ngurah Jelantik; Kristina Bedinan; Imanuel Benu (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2022)
The purpose of this experiment was to evaluate the herbage production and energy value of Suket putihan grass (Bothriochloa pertusa) harvested at different ages. The experiment was carried out following a completely randomize design with 3 treatments and 3 replications. The treatments consisted of different defoliation ages of Suket putihan grass (Bothriochloa pertusa), i.e. respectively at 40 days (BP40), 60 days (BP60), 80 days (BP80). The observed variables included the dry matter (DM) production, stem leaf ratio, In vitro digestibillity and energy value. Result showed that the defoliaton age had a significant effect (P<0.05) on dry matter production, stem leaf ratio, dry matter digestibillity and had a very significant effect (P<0.01) on the organic matter digestibillity and energy value of Suket putihan grass (Bothriochloa pertusa). The DM production of Suket Putihan grass (Bothriochloa pertusa) increased with increasing defoliation age, while its In vitro digestibility and energy value decreased due to the high stem to leaf ratio and increased harvesting time. In conclusion, the best defoliation time for B. pertusa is between 40 and 60 days after planting.